2020
DOI: 10.1002/app.50295
|View full text |Cite
|
Sign up to set email alerts
|

Economical conductive graphite‐filled polymer composites via adjustable segregated structures: Construction, low percolation threshold, and positive temperature coefficient effect

Abstract: The economical graphite‐filled thermoplastic urethane/ultra‐high molecular weight polyethylene (TPU/UHMWPE) composites with the segregated structure were constructed by the combination of mechanical crushing and melt blending method. The low percolation threshold of 1.89 wt% graphite in the adjustable segregated composites was obtained and high electrical conductivity was about 10−1 S m−1 at 10 wt% graphite loadings owing to the formation of three‐dimensional conductive networks. Moreover, when the graphite lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…This finding can be explained considering that, due to the segregated morphology of the UHMWPE/ETC systems, the increase of particle loadings does not promote an increment of the polymer/particles interfacial area. More in detail, in the composites containing 1 wt% of ETC, the formation of particle‐rich channels occurs, inducing some restrains of the relaxation process of UHMWPE macromolecules and an increase of the low‐frequency complex viscosity 46,47 . The addition of higher amounts of ETC causes a modest rise of the complex viscosity, as the introduced particles contribute to the increase of the particle path thickness only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding can be explained considering that, due to the segregated morphology of the UHMWPE/ETC systems, the increase of particle loadings does not promote an increment of the polymer/particles interfacial area. More in detail, in the composites containing 1 wt% of ETC, the formation of particle‐rich channels occurs, inducing some restrains of the relaxation process of UHMWPE macromolecules and an increase of the low‐frequency complex viscosity 46,47 . The addition of higher amounts of ETC causes a modest rise of the complex viscosity, as the introduced particles contribute to the increase of the particle path thickness only.…”
Section: Resultsmentioning
confidence: 99%
“…More in detail, in the composites containing 1 wt% of ETC, the formation of particle-rich channels occurs, inducing some restrains of the relaxation process of UHMWPE macromolecules and an increase of the low-frequency complex viscosity. 46,47 The addition of higher amounts of ETC causes a modest rise of the complex viscosity, as the introduced particles contribute to the increase of the particle path thickness only.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the processing technology for CPCs with specific structures was usually complicated. For example, in our previous reports, 35 based on the segregation system on thermoplastic polyurethanes/ultra-high molecular weight polyethylene-flake graphite (TPU/ UHMWPE-FG) composites by the melt blending, the low percolation threshold (1.89 wt% of FG) and good PTC effects could be achieved. However, the processing technology in this system was complex, restricting the practical application.…”
Section: Introductionmentioning
confidence: 99%
“…However, in molding these polymers, certain pressure has to be applied due to the extremely poor melt fluidity. For example, the thermoplastic polyurethanes (TPU)/UHMWPE‐graphite composites were constructed by mechanical crushing and hot‐pressing method 31 . Li et al reported a segregated structure was constructed for POE/multi‐walled CNT (MWCNT) elastomeric conductive composites with chemically cross‐linked POE granules under a pressure of 10 MPa 32 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the thermoplastic polyurethanes (TPU)/UHMWPE-graphite composites were constructed by mechanical crushing and hot-pressing method. 31 Li et al reported a segregated structure was constructed for POE/multi-walled CNT (MWCNT) elastomeric conductive composites with chemically crosslinked POE granules under a pressure of 10 MPa. 32 In addition, in order to improve the mechanical strength of the s-CPCs, a third material is usually needed to act as interfacial bonding.…”
Section: Introductionmentioning
confidence: 99%